Cross-Cultural Adaptation and Validation of the Chinese Version of the Brace Questionnaire - Yi, Honglei; Chen, Hu; Wang, Xinhui; Xia, Hong (Frontiers in Pediatrics, 2022)
Objective. To adapt the questionnaire cross-culturally and to analyze the adaptation and validation of the Chinese version of the Brace Questionnaire (C-BrQ). Methods. The adaptation was based on the International Quality of Life Assessment Project guidelines. A total of 79 patients with AIS were included to examine the psychometric properties of the C-BrQ. The reliability was assessed using internal consistency (the Cronbach’s alpha coefficient) and test-retest reliability (intraclass correlation coefficient ICC2.1, 95%CI). And floor and ceiling effects were calculated. Lin's Concordance Correlation coefficient (CCC, 95%CI) was used to compare the agreement between Scoliosis Research Society-22 patient questionnaire (SRS-22) and C-BrQ. Results. There were strong correlations between each item and its corresponding domain significantly. The correlations between the C-BrQ domains and their related questions vary from moderate to strong (r =0.311 to 0.933, P＜0.05). The Cronbach’s was 0.891, showing good internal consistency of each domain of the BrQ and the ICC in test-retest was 0.860(0.8776,0.912), which means an excellent test-retest reliability. The Lin's CCC, between SRS-22 and C-BrQ was 0.773 (0.669,0.848), showing great agreement. However, no significant floor effect and ceil effect in C-BrQ was observed, except ceiling effect in school activity and bodily pain. Conclusion. BrQ was translated and cross-culturally adapted for use in China with good internal consistency and excellent test-retest reliability.